Visible light antibacterial potential of graphene-TiO₂ cementitious composites for self-sterilization surface - Hamdany, Abdul Halim (2023)
Graphene oxide-titanium dioxide (GO-TiO2) composite was synthesized with one step hydrothermal process. The structure and morphology were characterized by field-emission-scanning-electron-microscopy, Thermogravimetric analysis, X-ray diffraction, Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy. Photocatalytic activity against Escherichia coli inactivation was carried out by GO-TiO2 mixed with cement composite under visible light. The result revealed no significant difference between morphology of GO-TiO2 and pristine TiO2. FESEM and FTIR results showed the presence of carbon component in the GO-TiO2 composites. TGA-IR confirmed that the GO content (3%) in the composite could be controlled during the synthesis process. The synthesized GO-TiO2 had stronger visible light absorption and narrower bandgap (3.11 eV) than TiO2 (3.21 eV). The bandgap reduction was also observed in cement sample with GO-TiO2 (3.08 eV) which could be beneficial for reducing the energy needed for photoexcitation. As a result, the specimen with GO-P25 outperformed specimens with others for Escherichia coli inactivation.